FRI0190 Safety of certolizumab pegol in rheumatoid arthritis patients with previous hepatitis b virus exposure. (23rd January 2014) - Bello, S.; Fanizzi, R.; Serafino, L.; Albanese, L.; Bonali, C.; Lapadula, G.
Abstract : Objectives: TNFα is a key cytokine in the integrated host defence system against infectious diseases, acting on both the innate and the adaptive immune system. Anti-TNF agents may elicit Hepatitis B Virus (HBV) reactivation in patients with positive serology for HBV markers. Few data regarding the safety of these agents in the setting of chronic viral infections are available, and these are mainly based on case reports. According to our knowledge this is the first retrospective analysis on safety of certolizumab pegol in patients with previous HBV exposure. Methods: Among 35 patients with rheumatoid arthritis treated with certolizumab pegol in a single center of the southern Italy, we identified 10 patients with previous documented HBV exposure, 2 male and 8 female with average age 55, 5 years old; 8/10 resulted RF+, 4/10 RF+ and anti-CCP+. 8 were treated with DMARDs (6 methotrexate 10-15 mg/week, 1 cyclosporine A 150 mg/day, 1 idroxyclorochine 200 mg/day+ salazopyrin 1000mg/day) and 1 with mesalazine 800 mg/day. 9/10 were treated also with corticosteroids at low dosage (prednisone 2, 5-12, 5 mg/day, mean 5.5). 9 patients were HBsAg- and HBV serology was respective anti-HBs+ (8/9), HBeAg- (9/9), anti-HBe- (6/9), anti-HBc IgM- (9/9), anti-HBc IgG+ (6/9). 1 patient resulted HBsAg+, anti-HBs-, HBeAg-, anti-HBe+, anti-HBc IgM- and anti-HBc IgG+, and was on treatment with entecavir 0, 5 mg/day since 3 years. Disease activity, inflammatory markers, transaminase levels, HBV markers and HBV-DNA where periodically monitored according to the local standard of care. Results: Patients were monitored from 3 to 22 months (overall 110 months, mean 11 months). On this period none of the patients showed variation in HBV markers with stable anti-HBs titre (mean 761 vs 697mlU/ml); only 1 patient showed an increase in GPT (<x3 reference value) that decrease when methotrexate therapy was stopped; concomitant increase in HBV DNA was excluded. Of some patients were available more than one HBV DNA evaluation performed after 12-18 months of therapy (mean 15, 3 months) without evidence of HBV replication. Disease activity measures decreased (mean DAS28 5, 01 vs 4, 02; mean VES: 45, 1 vs 28, 4; mean PCR: 21, 95 vs 12, 99 mg/L) during the monitoring period. Conclusions: Into a cohortof patients with rheumatoid arthritis and treated with certolizumab pegol, 28.5% showed a previous contact with HBV. Therapy with certolizumab pegol showed to be safe although performed in combination with DMARDs and steroids and in the observation period HBV reactivation was not recorded in any patient. In one HBV inactive carrier patient the association therapy with certolizumab pegol and entecavir showed safety and efficacy for 12 months. Disclosure of Interest: None Declared